2011
DOI: 10.1016/j.biocontrol.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ground-cover management on spider mites and their phytoseiid natural enemies in clementine mandarin orchards (II): Top-down regulation mechanisms

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 49 publications
4
62
0
2
Order By: Relevance
“…In this logic, results obtained with F. arundinacea in this study provide at least one plausible explanation for the field results obtained by Aguilar-Fenollosa et al (2011a;2011b) and reassure that F. arundinacea is a cover crop that should be encouraged in citrus orchards. Results showed that the phytoseiids exhibited a similar spatial distribution pattern under different prey densities.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this logic, results obtained with F. arundinacea in this study provide at least one plausible explanation for the field results obtained by Aguilar-Fenollosa et al (2011a;2011b) and reassure that F. arundinacea is a cover crop that should be encouraged in citrus orchards. Results showed that the phytoseiids exhibited a similar spatial distribution pattern under different prey densities.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, not only the phenology of the ground cover (Aguilar-Fenollosa et al 2011b) but also the quality of the food source provided (pollen and others) by this ground cover could have a serious impact on phytoseiid dynamics and abundance, and therefore in pest control. In this logic, results obtained with F. arundinacea in this study provide at least one plausible explanation for the field results obtained by Aguilar-Fenollosa et al (2011a;2011b) and reassure that F. arundinacea is a cover crop that should be encouraged in citrus orchards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre ellos, destacan los ácaros depredadores de la familia de los Phytoseiidae (Mesostigmata) (Abad-Moyano et al, 2009a;Aguilar-Fenollosa et al, 2011b;Aguilar-Fenollosa et al, 2012).…”
Section: Enemigos Naturalesunclassified
“…Es el fitoseido más abundante en los cítricos españoles, tanto en los árboles como en la flora adventicia asociada a los mismos (GarciaMarí et al, 1991;Abad-Moyano et al, 2009a;Aguilar-Fenollosa et al, 2011b). Además, se le considera una especie palinófaga ya que es capaz de sobrevivir alimentándose únicamente de polen e incluso mantenerse a densidades relativamente altas en el cultivo cuando las presas son escasas .…”
Section: Phytoseiidaeunclassified